Betaine attenuates sodium arsenite-induced renal dysfunction in rats. (2nd November 2022) - Sharma, Sumedha; Kaur, Tajpreet; Sharma, Ashwani Kumar; Singh, Balbir; Pathak, Devendra; Yadav, Harlokesh Narayan; Singh, Amrit Pal
Abstract: Exposure to higher levels of arsenic is a serious threat affecting human health worldwide. We investigated the protective role of betaine (N, N, N-trimethylglycine) against sodium arsenite-induced renal dysfunction in rats. Sodium arsenite (5 mg/kg, oral) was given to rats for 4 weeks to induce nephrotoxicity. Betaine (125 and 250 mg/kg, oral) was administered in rats for 4 weeks along with sodium-arsenite feeding. Arsenic-induced renal dysfunction was demonstrated by measuring serum creatinine, creatinine clearance, urea, uric acid, potassium, fractional excretion of sodium, and microproteinuria. Oxidative stress in rat kidneys was determined by assaying thiobarbituric acid reactive substances, superoxide anion generation, and reduced glutathione levels. Furthermore, hydroxyproline assay was done to assess renal fibrosis in arsenic intoxicated rats. Hematoxylin-eosin and picrosirius red staining revealed pathological alterations in rat kidneys. Renal endothelial nitric oxide synthase (eNOS) expression was determined by immuno-histochemistry. Concurrent administration of betaine abrogated arsenic-induced renal biochemical and histological changes in rats. Betaine treatment significantly attenuated arsenic-induced decrease in renal eNOS expression. In conclusion, betaine is protective against sodium arsenite-induced renal dysfunction, which may be attributed to its anti-oxidant activity and modulation of renal eNOS expression in rat kidneys.